Validity of the Postoperative Morbidity Survey after abdominal aortic aneurysm repair—a prospective observational study. Issue 1 (December 2015) - Goodman, Ben; Batterham, Alan; Kothmann, Elke; Cawthorn, Louise; Yates, David; Melsom, Helen; Kerr, Karen; Danjoux, Gerard
Abstract Background Currently, there is no standardised tool used to capture morbidity following abdominal aortic aneurysm (AAA) repair. The aim of this prospective observational study was to validate the Postoperative Morbidity Survey (POMS) according to its two guiding principles: to only capture morbidity substantial enough to delay discharge from hospital and to be a rapid, simple screening tool. Methods A total of 64 adult patients undergoing elective infrarenal AAA repair participated in the study. Following surgery, the POMS was recorded daily, by trained research staff with the clinical teams blinded, until hospital discharge or death. We modelled the data using Cox regression, accounting for the competing risk of death, with POMS as a binary time-dependent (repeated measures) internal covariate. For each day for each patient, 'discharged' (yes/no) was the event, with the elapsed number of days post-surgery as the time variable. We derived the hazard ratio for any POMS morbidity (score 1–9) vs. no morbidity (zero), adjusted for type of repair (endovascular versus open), age and aneurysm size. Results The hazard ratio for alive discharge with any POMS-recorded morbidity versus no morbidity was 0.130 (95 % confidence interval 0.070 to 0.243). The median time-to-discharge was 13 days after recording any POMS morbidity vs. 2 days after scoring zero for POMS morbidity. Compliance with POMS completion was 99.5 %. Conclusions The POMS is a valid tool for capturing short-term postoperative morbidity following elective infrarenal AAA repair that is substantial enough to delay discharge from hospital. Daily POMS measurement is recommended to fully capture morbidity and allow robust analysis. The survey could be a valuable outcome measure for use in quality improvement programmes and future research.